Spiritual Emotional Freedom Technique and Lavender Aromatherapy in Hypertensive Elderly: A Quasy-Experimental Study - Ni Luh Putu Dian Yunita Sari; I Kadek Prastikanala (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Hypertensive elderly are one of the vulnerable groups because they have the potential to experience catastrophic disease complications and even death. Efforts to control blood pressure and pain perception in elderly hypertension require a drug companion approach. The purpose of this study was to determine the combination of Spiritual Emotion Freedom Technique (SEFT) and lavender aromatherapy on blood pressure and pain scale of hypertensive elderly. Methods: A quasi-experimental design with control group pre post-test was used in this study. The population in this study were all elderly people with hypertension who visited the Geriatric Poly of Mangusada General Hospital, which were then selected using purposive sampling technique. The sample size obtained after calculation using a two-group unpaired approach was 70 people. A calibrated sphygmomanometer was used to measure blood pressure, while the Numeric Rating Scale (NRS) was used to measure the pain scale. The analysis test used in paired data is Wilcoxon sign rank and in unpaired data is Mann-Whitney because it is not normally distributed. This study was approved by the Ethics Committee for Health Research at Mangusada General Hospital, Badung Regency, Bali (Approval Number: 070/6857/RSDM/2024). All respondents provided informed consent before participating in the study. Results: There is a significant difference between the intervention group and the control group on systolic (mean difference = 9,914), diastolic (mean difference = 3,714), and the pain scale (mean difference = 1,057) of hypertensive elderly before and after the intervention. So, there is an effect of the combination of Spiritual Emotion Freedom Technique (SEFT) and lavender aromatherapy on blood pressure and pain scale of hypertensive elderly. Conclusion:These results can be used as a reference in providing interventions for hypertensive elderly to control blood pressure and reduce pain scale.